2013
DOI: 10.1002/ffj.3140
|View full text |Cite
|
Sign up to set email alerts
|

Lipase: A potential biocatalyst for the synthesis of valuable flavour and fragrance ester compounds

Abstract: Biocatalysis has attracted special attention for the synthesis of industrially valuable ester compounds. This review focuses mainly on lipases obtained from different sources (commercially available or newly isolated) as biocatalysts for the synthesis of flavour and fragrance esters in solvent‐free as well as in non‐aqueous reaction media (i.e. organic and neoteric solvents). Neoteric solvents such as ionic liquids and supercritical fluids are greener and environmentally benign; their use in lipase‐catalysed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 132 publications
0
84
0
6
Order By: Relevance
“…It has been shown that lipase-mediated esterification reaction is influenced by several parameters such as molar ratio of acid to alcohol, type of applied solvent and temperature of reaction mixture (Dhake et al, 2013). In order to evaluate the effect of molar ratio of acid to alcohol on the esterification assisted by the partially purified lipase of B. atrophaeus FSHM2, various molar ratios were applied in the reaction mixtures.…”
Section: Partial Purification Of Lipasementioning
confidence: 99%
“…It has been shown that lipase-mediated esterification reaction is influenced by several parameters such as molar ratio of acid to alcohol, type of applied solvent and temperature of reaction mixture (Dhake et al, 2013). In order to evaluate the effect of molar ratio of acid to alcohol on the esterification assisted by the partially purified lipase of B. atrophaeus FSHM2, various molar ratios were applied in the reaction mixtures.…”
Section: Partial Purification Of Lipasementioning
confidence: 99%
“…In this sense, it should be noted that nonpolar solvents have been reported as less harmful to the enzyme than highly polar ones (Rodrigues and Fernandez-Lafuente, 2010a;Dhake et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…In particular, several flavors (short and long chain aliphatic esters) of industrial interest have been obtained by esterification, transesterification or interesterification reactions using lipases (Gandhi, 1997;Alcantara et al, 1998;Abbas and Comeau, 2003;Silva and Jesus, 2003;Hasan et al, 2006), with applications in juices, cheeses, baked goods, candies and beverages, for instance (Mahapatra et al, 2009). The demand for these chemicals has continuously increased at the rate of 4.3% per year (Dhake et al, 2013). Rodrigues and Fernandez-Lafuente (2010b) and Dhake et al (2013) presented relevant reviews concerning the wide application of lipases for the synthesis of flavors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipases are widely used because of their ready availability, low cost of production, utility in food, biotechnology, and pharmacology [61]. Novel biotechnological applications have been successfully established using lipases for the synthesis phenolic lipids, the production of pharmaceuticals, agrochemicals, and lavor compounds [52,62,63]. Moreover, the use of lipases in the food industry is increasing due to the need for the production of esters, biodegradable polyesters, and speciic FAs [64].…”
Section: Deinition Sources and Applicationsmentioning
confidence: 99%